2021
DOI: 10.3892/or.2021.8189
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA TINCR attenuates the proliferation and invasion, and enhances the apoptosis of cutaneous malignant melanoma cells by regulating the miR‑424‑5p/LATS1 axis

Abstract: Cutaneous malignant melanoma (CMM) is responsible for ≥1/2 of skin cancer-related mortalities. The aberrant expression of long non-coding RNAs (lncRNAs) has been associated with the development of CMM. However, to the best of our knowledge, the role of the lncRNA TINCR ubiquitin domain containing (TINCR) in CMM has not been previously investigated, and thus, the current study aimed to evaluate this in vitro and in vivo . Reverse transcription-quantitative PCR (RT-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…By contrast, RASSF1A, an upstream activator of MST2, and LATS1, a downstream substrate of MST2, may work as tumour suppressors. RASSF1A expression is commonly lost in melanoma patients (Reifenberger et al, 2004), and the expression of LATS1 is often downregulated (Han et al, 2021, Yuan et al, 2015). These observations are consistent with a tumour suppressive function of MST2 signalling that is independent of YAP1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, RASSF1A, an upstream activator of MST2, and LATS1, a downstream substrate of MST2, may work as tumour suppressors. RASSF1A expression is commonly lost in melanoma patients (Reifenberger et al, 2004), and the expression of LATS1 is often downregulated (Han et al, 2021, Yuan et al, 2015). These observations are consistent with a tumour suppressive function of MST2 signalling that is independent of YAP1.…”
Section: Discussionmentioning
confidence: 99%
“…RASSF1A is commonly lost in melanoma patients due to DNA methylation (Reifenberger et al, 2004). LATS1 levels seem to be decreased through different mechanism that include post-translational modification and long non-coding RNAs (Han et al, 2021, Yuan et al, 2015). These results suggest that loss of a functional MST2 pathway might be associated with melanoma development.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that Fulvestrant treatment reduced ERα and VEGF expressions in primary vascular endothelial cells might suggest that Fulvestrant ameliorated inflammation. The miRNA regulatory member i.e., miR-424 is a widely studied factor, and it regulates the proliferation or growth of human cancer cells, including liver cancer, melanoma, and colorectal cancer, through the target genes [21]. It blocked E2-mediated cell multiplication in endometrial carcinoma by targeting G protein-coupled ER.…”
Section: Discussionmentioning
confidence: 99%
“…Recent transcriptomic studies revealed that lncRNAs might be engaged in regulating phenotype switches in melanoma. One is the lncRNA TINCR, whose ectopic expression reduces melanoma cell invasion and expression of invasive markers, driving the transition of invasive cells to intermediate and proliferative cell states [44,140]. TINCR is highly expressed in primary melanomas, is downregulated in metastatic melanomas, and is required to maintain the proliferative cell state.…”
Section: Lncrnas In the Phenotype Switching And Metastasis Formation ...mentioning
confidence: 99%
“…TINCR is highly expressed in primary melanomas, is downregulated in metastatic melanomas, and is required to maintain the proliferative cell state. TINCR downregulation inhibits melanoma development in vivo by suppressing the ATF4-CHOP pathway [44] and activating the Hippo pathway [140]. However, the association of TINCR expression with melanoma clinic-pathological features and prognosis is still missing.…”
Section: Lncrnas In the Phenotype Switching And Metastasis Formation ...mentioning
confidence: 99%